Recent Advancements in Typical Friedel–Crafts Alkylation Reactions Focused on Targeting Arene Nucleophiles - Singh, Sanjay; Hazra, Chinmoy K. (Synthesis, 2023)
This review delves into recent advances and significant breakthroughs in the field of the catalytic Friedel–Crafts alkylation of targeted arenes or heteroarenes. Though a few earlier literatures are referenced, the main emphasis of this review focuses on the literature mainly published between 2015 and March 2023.1 Introduction2 History and Background3 Alcohols as Alkylating Agents4 Aldehydes and Ketones as Alkylating Agents5 Alkyl Fluorides as Alkylating Agents6 Epoxides as Alkylating Agents7 Cyclopropanes as Alkylating Agents8 Conclusion and Outlook
Keywords: Friedel–Crafts; organocatalytic; alkylating agents; asymmetric catalysis; arenes/heteroarenes